Use of Z-Codes to Record Social Determinants of Health Among Fee-for-service Medicare Beneficiaries in 2017. - Weeks, William B.; Cao, Stacey Y.; Lester, Chris M.; Weinstein, James N.; Weinstein, James N.; Morden, Nancy E.; Morden, Nancy E.; Weinstein, James; Weeks, Bill (Journal of General Internal Medicine, 2020)
Abstract